Infection of an axillo-bifemoral bypass graft following intravesical bacillus Calmette–Guerin (BCG) immunotherapy for urothelial cancer due to Mycobacterium bovis and Staphylococcus aureus. (December 2016) - DeSimone, Daniel C.; Tande, Aaron J.
Abstract: We report a case of occult Mycobacterium bovis left axillary-bifemoral bypass graft infection, with superimposed acute methicillin-susceptible Staphylococcus aureus (MSSA) infection in an 82 year old male following intravesicular bacillus Calmette–Guerin (BCG) for adjuvant therapy of urothelial cancer. The patient underwent partial removal of the bypass graft and treated with antimycobacterial therapy—rifampin and isoniazid for 9 months, and intravenous cefazolin followed by oral cephalexin for chronic suppressive therapy for MSSA. This presentation highlights the need to consider indolent infection masquerading as mechanical erosion, even when an alternate infection is present.